The Public Sector Governance Reform Cycle : Available Diagnostic Tools - Wilhelm, Vera; Kushnarova, Inna (World Bank, Washington, DC, 2012)
Developing more efficient, transparent public institutions in the Bank's client countries requires a two-pronged approach. First, countries must build their capacity to perform functions such as policymaking and policy implementation, regulation, service delivery, and administrative management. Second, they must enhance the state's accountability-both internally, among the executive, legislative, and judicial branches, and externally, to citizens, users of public services, and other stakeholders. Initiatives in both areas contribute to good governance, understood as the exercise of public authority for the common good. To succeed, this approach must be based on a solid diagnosis of the weaknesses it is trying to address, accompanied by awareness and buy-in from citizens, politicians, and the international community.